Limits to international banking consolidation - Hans Peter Grüner; Falko Fecht (Deutsche Bundesbank, 2006)
Heterogenous banking supervision and regulation is often considered as the most important impediment for Pan-European Bank mergers. In this paper we identify other more fundamental reasons for a limited degree of cross-country integration in retail banking. We argue that the distribution of regional liquidity shocks may pose a natural limit to the extent of cross-border bank mergers. The paper derives the impact of different underlying stochastic structures on the optimal structure of cross regional bank mergers. Imposing a symmetry restriction on the underlying stochastic structure of liquidity shocks we find that benefits from diversification and the costs of contagion may be optimally traded off if banks from some but not from all regions merge. Under an additional monotonicity assumption full integration is only desirable if the number of regions with diverse risks is sufficiently large.
Keywords: D61; E44; G21; 330; Bank Mergers; Financial Integration; Liquidity Transformation; Liquidity Crisis; Risk Sharing; Retail Banking; Internationale Bank; Bankenliquidität; Mehr-Länder-Modell; Bank; Marktintegration; Theorie